Effect of Minamil on the Growth Performance and Age at Maturity of Ghungroo Pigs in Field Condition in Zunheboto District - CHAURASIA, RAKESH KUMAR (Indian Journal of Hill Farming, 2014)
Vitamin and minerals plays an important role in the growth performances in Pigs reared in traditional system. Pig farmers depend mainly on the kitchen waste mixed with wheat bran and maize as well as locally available fodder crops to feed their piglets. Considering the importance of vitamin and mineral in pig diet an experiment was conducted to find out the effect of minamil on the performance of Pigs. The result obtained showed that minamil had a significant effect on the age at onset of heat but no effect on body weight gain.